Measuring Consumer Engagement in Omnichannel Retailing: The Mobile In-Store Experience (MIX) Index - Lawry, Charles Aaron; Bhappu, Anita D. (Frontiers in Psychology, 2021)
We draw insights from Activity Theory within the field of human-computer interaction to quantitatively measure a mobile in-store experience (MIX), which includes the suite of shopping activities and retail services that a consumer can engage in when using their mobile device in brick-and-mortar stores. We developed and validated a nine-item, formative MIX index using survey data collected from fashion consumers in the United States (n = 1,267), United Kingdom (n = 370), Germany (n = 362), and France (n = 219). As survey measures of consumer engagement in omnichannel retailing using a mobile device, the index items with stronger factor loadings described in-store shopping activities whereas those with weaker factor loadings described activities related to behavioral targeting and social networking. These results suggest that retailers should give consumers the autonomy to independently find, evaluate and purchase merchandise in brick-and-mortar stores, thereby enabling them to co-create personalized shopping experiences as active participants within an omnichannel retail servicescape. Our findings also suggest that retailers should provide consumers with more authentic ways to build community and brand affiliations than mobile marketing and social media promotions. In-store activities should not simply be a migration of pre-existing e-commerce capabilities onto mobile devices. An engaging mobile in-store experience should be an amalgam of physical and digital activities that produce a seamless shopping journey and leverage the unique properties of mobile devices – ultra-portability, location sensitivity, untetheredness, and personalization. Retail executives can use the validated MIX index to prepare strategic investments in mobile technology applications and capabilities for retail stores within their omnichannel operations. The nine-item MIX index is also well-suited for consumer surveys, which also makes it an attractive measure of consumer engagement in omnichannel retailing for future academic research.